2016
DOI: 10.1021/acs.biomac.6b01148
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Hydrogel Prepared Using a PEG/Vitamin E Copolymer Facilitating Aqueous-Driven Gelation

Abstract: Hydrogels have been widely explored for biomedical applications, with injectable hydrogels being of particular interest for their ability to precisely deliver drugs and cells to targets. Although these hydrogels have demonstrated satisfactory properties in many cases, challenges still remain for commercialization. In this paper, we describe a simple injectable hydrogel based on poly(ethylene glycol) (PEG) and a vitamin E (Ve) methacrylate copolymer prepared via simple free radical polymerization and delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…This data shows that the gelling time for all the formulations is enough to allow the alignment of CNC ( Figure 2D). This timerange is similar to other in situ gelling injectable formulations proposed for tissue engineering applications 40,41,41 . With respect to isotropic hydrogels bulk viscoelastic properties ( Figure 3B), data exhibited an increase in the elastic modulus (G') value proportional to the concentration of nanoparticles used.…”
Section: Characterization Of Gelatin Nanocomposite Constructssupporting
confidence: 74%
“…This data shows that the gelling time for all the formulations is enough to allow the alignment of CNC ( Figure 2D). This timerange is similar to other in situ gelling injectable formulations proposed for tissue engineering applications 40,41,41 . With respect to isotropic hydrogels bulk viscoelastic properties ( Figure 3B), data exhibited an increase in the elastic modulus (G') value proportional to the concentration of nanoparticles used.…”
Section: Characterization Of Gelatin Nanocomposite Constructssupporting
confidence: 74%
“…Ceftriaxone or Oxaliplatin drugs were directly synthesized with organo-hydrogel [ 18 ]. The synthesis of drug-loaded organo-hydrogels was the same as the synthesis procedure of the organo-hydrogels described above.…”
Section: Methodsmentioning
confidence: 99%
“…The degradation and, thus, the drug delivery kinetics of the hydrogel were controllable via the degree of hydration of the hydrogels. [52] In another study, Ding et al reported injectable silk nanofiber hydrogels for controlled drug release and vascularization. The silk nanofiber hydrogels were prepared by physical interactions between silk nanofibers with the drug, desferrioxamine.…”
Section: Physically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%